Satellite Remote Sensing in Landuse Planning of Arid Environment - Singh, Surendra; Sharma, K D; Bohra, D N (Annals of Arid Zone, 2016)
Satellite remote sensing using IRS-1A (LISS-1) False Colour Composites (FCCs) of kliarifand rabi seasons for the year 1988-89 in conjunction with ground truth enabled to identify and to map different landusenand cover categories at levels I and II in Jodhpur district comprising an area of 22,85.000 ha of and northwestern Rajasthan. The extent of different landuselland cover categories from IRS FCC products and revenue record has been computed and tabulated. It has been observed that the area mapped from IRS FCC products for all the landusenand cover categor esis less than that of revenue record due to the small scale and poor resolution of the remotely sensed data. The suitable croppingpatterns, plant species and soil and water conservation measures have been sugested for the rational landuse planning of different landusenand cover categories of the district.